Katalis bimetalk CuCo/AI203 dalam reaksi hidrolisis sodium borohydride sebagai reaksi penghasil hidrogen - Huriyatul Husna; Hernowo Widodo (Institute for Advanced Social, Science, and Sustainable Future, 2024)
Background: Sodium Borohydrida is an inorganic compound with the chemical formula NaBH4, this compound is soluble in alcohol and some ether has not been added to air into hydrogen gas containing a catalyst. Findings: In this way it can be produced safely for fuel cells. Methods: Producing catalytically H2 from solution, NaBH4 has gained many advantages, NaBH4 is not flammable, environmentally friendly reaction products, the rate of generation of H2 is easily controlled, H2 can be produced at low temperatures. Conclusion: The catalyst used in the hydrolysis of sodium borohydride is Cu and Co which acts as a heterogeneous catalyst. The limited surface area of heterogeneous catalysts causes lower catalytic activity because catalyst activity is directly related to its surface area. Thus, the use of Cu and Co with large surfaces provides a potential route for increasing catalytic activity. For this reason, we use CuCo / Al2O3 as a catalyst in the hydrolysis of sodium borohydride.